Barabhas Machair: surveys of an eroding sandscape (Scottish Historical and Archaeological Internet Reports, 2018)
The townships of Barabhas are on the west coast of the Isle of Lewis, in the Outer Hebrides between the blanket bog of Barabhas Moor to the east, and machair and the Atlantic Ocean to the west. The Barabhas Machair (centre NGR: NB 351 513) has been eroding for at least a century, and of archaeological interest for nearly as long. Survey and excavations over the last 40 years have revealed settlements from the Early Bronze Age to the present day, in a landscape that has been used and reused.